Perspectives of Teachers and Students on Online Religious Education during the COVID-19 Pandemic - Kouzeli, Ariadni; Tsirevelos, Nikolaos; Karamouzis, Polikarpos (Greek Journal of Religious Education (GjRE), 2025)
This paper investigates the views of theology teachers and students regarding distance learning in the Religious Education course during the COVID-19 pandemic. It consists of a theoretical and research methodology section. The theoretical background includes a) Religious Education in Greece, b) the concept of distance learning, c) the teacher’s role in online education, d) implementation of distance learning in Greek schools during the pandemic, e) teachers’ perspectives, and f) students’ perspectives. The research adopts a qualitative methodology, using interviews with sixteen secondary education theology teachers. Data was analyzed using content analysis by category. The study explores how teachers adapted to digital teaching and how students responded. Key questions include participation levels, engagement with the subject, and digital literacy among both educators and learners. Findings indicate that digital tools, when used pedagogically, enhanced students’ interest in Religious Education without compromising educational quality.